Leadership Model of the Nurul Barokah Cikijing Majalengka Islamic Boarding School Kyai: (Between Tradition and Innovation) - Ahmad Sahid, Toto; Ahmad Yani; Nina Karlina; Ari Yandi Hidayat (The Future of Education Journal, 2024)
This study examines the leadership model of kyai at the Nurul Barokah Islamic Boarding School, Cikijing, Majalengka, which is known as a salafiyah Islamic boarding school with the characteristics of sorogan, bandungan, and yellow book learning traditions. Since its establishment in 1984, this Islamic boarding school has combined tradition-based education with modern innovations, such as the establishment of formal schools (RA, SD, SMP, SMA), tahfidz programs, and Job Training Centers (BLK) in the fields of sewing, farming, and technology training. This Islamic boarding school also involves more than 713 active students and has produced thousands of alumni who have contributed as scholars, community leaders, and professionals in various fields. The study aims to explore the leadership model applied at the Nurul Barokah Islamic Boarding School, Cikijing, Majalengka, with a focus on the interaction between tradition and innovation. This study is expected to provide insight into how traditional values ​​can integrate with modern demands without sacrificing the essence of Islamic boarding schools as Islamic educational institutions. The research method uses a descriptive qualitative approach through in-depth interviews, observation, and documentation. The results of the study indicate that kyai play a central role as a religious-paternalistic leader with a charismatic and visionary character. This leadership model integrates Islamic values ​​with adaptation to modern challenges, creating a harmonious and relevant educational environment. Traditions are maintained, while innovations such as the application of information technology and santri empowerment programs broaden the santri's horizons in facing the global era. The conclusion of the study confirms that the integration of tradition and innovation at the Nurul Barokah Islamic Boarding School is able to maintain the identity of the Islamic boarding school while producing religious individuals, broad-minded, and ready to compete globally. This model can be an inspiration for the development of other Islamic boarding schools in Indonesia.